THE EFFECT OF THE E-COMIC-ASSISTED PROBLEM BASED LEARNING (PBL) MODEL ON STUDENTS' CRITICAL THINKING AND ARGUMENTATION SKILLS ON PETROLEUM MATERIALS - Marhana Rezkiana; Asrial; M. Naswir (SOSIOEDUKASI, 2026)
The background of this research is based on the low level of students' higher-order thinking skills, especially critical thinking and argumentation skills, due to the teacher-centered learning process and minimal use of interesting and contextual media. This study aims to determine the effect of the Problem Based Learning (PBL) model assisted by e-comics on students' critical thinking and argumentation skills on petroleum material. The study used a quasi-experimental method with a nonequivalent control group design. The research sample consisted of an experimental class learning with the PBL model assisted by e-comics and a control class using conventional learning. The research instruments were critical thinking ability tests, argumentation ability tests, and observation sheets for teacher and student activities. The results showed that the application of the PBL model assisted by e-comics had a significant effect in improving students' critical thinking and argumentation skills compared to conventional learning. Students in the experimental class showed higher improvements in their ability to analyze, evaluate information, construct arguments, provide supporting evidence, and draw logical conclusions. E-comics media contributed to facilitating the understanding of abstract petroleum concepts through engaging narrative visualization. Thus, the e-comic-assisted PBL model is effective in improving students' critical thinking and argumentation skills on petroleum material.